Al-Qur’an dan Sunnah: Meluruskan Pemahaman Jihad dan Terorisme di Masyarakat - Sarli Amri Teguh Pribadi (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2021)
Allah swt sent Prophet Muhammad saw to bring Islam in the midst of humans as a blessing, and it is a great pleasure for humans not a calamity that brings calamity. The acts of terror carried out by terrorists are not in accordance with the teachings of the Islamic religion which always upholds the value of togetherness and respect among human beings. Islam in the Koran never teaches its people to be harsh towards others even though he is an infidel. Not only that, the sending of the prophet Muhammad is calling on us to always follow the teachings that the prophet Muhammad taught in his sunnah. Didn't the prophet Muhammad saw never teach his followers to terrorize other people, especially those who are weak.Keywords : Terror, Jihad, and Suicide Bombings.